Factors Influencing Opportunity Identification Of Entrepreneurs In Nigeria: The Roles Of Entrepreneurial Alertness And Social Media - Tunde, Odebunmi Abayomi (2022)
This study examines the relationship between entrepreneurial social network, entrepreneurial self-efficacy, prior knowledge, proactive personality, entrepreneurial creativity, and opportunity identification. This study also examines if entrepreneurial alertness and social media mediate and moderate the above relationship.